High levels of gut-homing immunoglobulin A+ B lymphocytes support the pathogenic role of intestinal mucosal hyperresponsiveness in immunoglobulin A nephropathy patients - Sallustio, Fabio; Curci, Claudia; Chaoul, Nada; Fontò, Giulia; Lauriero, Gabriella; Picerno, Angela; Divella, Chiara; Di Leo, Vincenzo; De Angelis, Maria; Ben Mkaddem, Sanae; Macchia, Luigi; Gallone, Anna; et al. (Nephrology, dialysis, transplantation, 2021)
Abstract Background Immunoglobulin A nephropathy (IgAN) is the most frequent primary glomerulonephritis. The role of the microbiota and mucosal immunity in the pathogenesis of IgAN remains a key element. To date, the hypothetical relationship between commensal bacteria, elevated tumour necrosis factor (TNF) superfamily member 13 [also known as B-cell activating factor (BAFF)] levels, perturbed homoeostasis of intestinal-activated B cells and intestinal IgA class switch has not been clearly shown in IgAN patients. Methods We studied the intestinal–renal axis connections, analysing levels of BAFF, TNF ligand superfamily member 13 (APRIL) and intestinal-activated B cells in IgAN patients, healthy subjects (HSs) and patients with non-IgA glomerulonephritides. Results IgAN patients had increased serum levels of BAFF cytokine, correlating with higher amounts of five specific microbiota metabolites, and high APRIL cytokine serum levels. We also found that subjects with IgAN have a higher level of circulating gut-homing (CCR9+ β7 integrin+) regultory B cells, memory B cells and IgA+ memory B cells compared with HSs. Finally, we found that IgAN patients had high levels of both total plasmablasts (PBs) and intestinal-homing PBs. Interestingly, PBs significantly increased in IgAN but not in patients with other glomerulonephritides. Conclusions Our results demonstrate a significant difference in the amount of intestinal-activated B lymphocytes between IgAN patients and HSs, confirming the hypothesis of the pathogenic role of intestinal mucosal hyperresponsiveness in IgAN. The intestinal–renal axis plays a crucial role in IgAN and several factors may contribute to its complex pathogenesis and provide an important area of research for novel targeted therapies to modulate progression of the disease. Graphical Abstract